From Prism to Kaleidoscope: Effect Versus Intention in the Conservation of Contemporary Art. Issue 2 (3rd July 2021) - Verbeeck, Muriel
ABSTRACT: Artist's intention is not an unambiguous concept in conservation. It is used to focus on the aesthetic function of the work and its intentional effect. To understand the artwork in order to transmit its meaning, the conservator must therefore become a "receptor" and "read" the stimuli created by the artist as objectively and sensitively as possible. This article includes a draft methodology ranging from taking inventory of the effects to documenting their nomenclature. Artist's intention can be seen as a prism, but for a complex artwork, conservators also need to use a kaleidoscope of perceptions.